Integration of GIS and RS techniques with empirically based approaches in soil loss and sediment yield modelling for the Magat watershed - Dimal, Matthew Oliver Ralp L.
Soil erosion is an environmental and economic problem that persists in many provinces of the Philippines. Short and long term damage associated with erosion have been known to occur on-site and off-site. These include nutrient degradation of soil which decreases agricultural productivity, increases pollution and salinity in rivers, and accelerates sedimentationof reservoirs that reduce power-generation capacities of hydro-electric power plants. Various models on soil erosion have been developed, but most of these approaches either require expansive and laborious field measurements or are based on numerous assumptions and low spatial and temporal resolution data that make spatial analysis trivial.